Exposure to phthalates among premenstrual girls from rural and urban Gharbiah, Egypt: A pilot exposure assessment study - Hablas Ahmed; Van Zomeren-Dohm Adrienne; Nahar Muna S; Calafat Antonia M; Soliman Amr S; Colacino Justin A; Seifeldin Ibrahim A; Rozek Laura S; Dolinoy Dana C (BMC, 2011)
Abstract Background Phthalates have been identified as endocrine active compounds associated with developmental and reproductive toxicity. The exposure to phthalates in premenstrual Egyptian females remains unknown. The objective of this study was to characterize phthalate exposure of a potentially vulnerable population of premenstrual girls from urban and rural Egypt. Materials and methods We collected one spot urine sample from 60 10-13 year old females, 30 from rural Egypt, and 30 from urban Egypt from July to October 2009. Samples were analyzed for 11 phthalate metabolites. Additionally, we collected anthropometrics as well as questionnaire data concerning food storage behaviors, cooking practices, and cosmetic use. Phthalate metabolite concentrations were compared between urban and rural Egyptians as well as to age and gender matched Americans. Results Monoethyl phthalate (MEP), was detected at the highest concentration in urine of Egyptian girls (median: 43.2 ng/mL in rural, 98.8 ng/mL in urban). Concentrations of urinary metabolites of di-(2-ethylhexyl) phthalate and dibutyl phthalate were comparable between Egyptians and age matched US girls. Storage of food in plastic containers was a statistically significant predictor of urinary mono-isobutyl phthalate (MiBP) concentrations when comparing covariate adjusted means. Conclusions Urinary concentrations of phthalate metabolites were similar in Egyptian and US populations, suggesting that phthalate exposure also occurs in developing nations. Dietary intake is likely an important route of exposure to phthalates in both urban and rural populations.